UJI AKTIVITAS ANTIBAKTERI FRAKSI ETIL ASETAT DAUN SENDUDUK (Melastoma affine D. Don) ASAL BENGKALIS TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Desi Linda Sari (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id)
Has been performed Antibacterial Activity Test Ethyl Acetate fraction of Leaf senduduk (Melastoma affine D. Don) Origin Bengkalis Against Staphylococcus aureus and Escherichia coli bacteria using fractionation and diffusion method. The purpose of this study was to determine the antibacterial activity of ethyl acetate fraction of leaf senduduk (Melastoma affine D. Don) from Bengkalis on the growth of Staphyloccus aureus and Escherichia coli bacteria. The result of antibacterial activity test from fraction of ethyl acetate of leaf senduduk (Melastoma affine D. Don) to Staphylococcus aureus bacteria with concentration of 60%, 45%, 30% and 15% showed the result of resistance diameter respectively 20,00 mm, 18,73 mm, 17.21 mm and 15.21 mm are included in the strong category. While the result of antibacterial activity test from fraction of ethyl acetate of leaf (Melastoma affine D. Don) to Escherichia coli bacteria with concentration of 60%, 45%, 30% and 15% showed the result of resistance diameter respectively 18,61 mm, 17, 48 mm, 15.28 mm and 12.23 mm are included in the strong to moderate category. As a positive control is used apaper disc Ciprofloxacin 5 µg. This indicates that the fraction of ethyl acetate leaves of the has antibacterial activity.